2y^2+27y+13=0 find answers by factorisation
Answers
Answered by
16
Hey KADAMV 2 ,
Here is your answer
-------------------------------------------------------
2y²+27y+13=0
Splitting the middle term
2y²+26y+1y+13
2y(Y+13) + 1(Y+13)
(2y+1)(Y+13)=0
2y+1=0 | y+13=0
2y= -1 | y= -13
Y= -1/2 | y=-13
Here is your answer
-------------------------------------------------------
2y²+27y+13=0
Splitting the middle term
2y²+26y+1y+13
2y(Y+13) + 1(Y+13)
(2y+1)(Y+13)=0
2y+1=0 | y+13=0
2y= -1 | y= -13
Y= -1/2 | y=-13
Answered by
8
2y^2+27y+13=0
2y^2+26y+y+13=0
2y(y+13)+1(y+13)=0
(2y+1)(y+13)=0
one answer is -1/2 and the other is -13
2y^2+26y+y+13=0
2y(y+13)+1(y+13)=0
(2y+1)(y+13)=0
one answer is -1/2 and the other is -13
Similar questions
English,
7 months ago
Math,
7 months ago
Political Science,
7 months ago
English,
1 year ago
Physics,
1 year ago
Math,
1 year ago
Psychology,
1 year ago